Magnetic and electric antennas calibration for partial discharge charge estimation in gas-insulated substations. (October 2022) - Mier, Christian; Rodrigo Mor, Armando; Castro, Luis; Vaessen, Peter
Graphical abstract: Highlights: Calibration method for partial discharges sensors in GIS. Recommendations for charge calibration constant estimation. Partial discharge charge estimation for magnetic and electric antennas in GIS. PD charge calibration for magnetic and electric antennas in a full-scale GIS. PD sensors harmonization for GIS. Abstract: There are no accepted procedures that quantify the apparent charge of partial discharge (PD) in gas-insulated substations (GIS). This paper proposes a calibration method for PD charge estimation using unconventional electromagnetic sensors: a magnetic loop antenna (inductive coupler) and an electric antenna (capacitive coupler.) The calibration procedure is intended for the voltage double integral method, which is reviewed for magnetic antennas and extended for electric antennas. By injecting low-frequency sinusoidal signals, the calibration constants are determined for two different test setups: the first one being a testbench where the characteristic impedance is matched and the second one a full-scale 420 kV GIS. The calibration method is validated in three ways: with a calibrated pulse in the testbench, a calibrated pulse in a full-scale GIS, and PD defects in the full-scale GIS. The calibration procedure revealed a frequency limit range dependent on the GIS length and the sensor's signal-to-noise ratio. The three validation methods showed low charge estimation errors for the magnetic and electric antennas, demonstrating that the PD calibration method applies to any electric/magnetic detector with a low-frequency derivative response. This research paves the way for better GIS insulation monitoring and PD sensor harmonization. © 2017 Elsevier Inc. All rights reserved.